Evaluation of Safety and Efficacy of Open Mini-Access Ureterolithotomy in the Era of Minimally Invasive Surgery - Meitei, Sholay Kangjam; Lodh, Bijit; Khumukcham, Somarendra; Gupta, Sandeep; Singh, Kaku Akoijam; Sinam, Rajendra Singh (Urology Journal, 2014)
Abstract Purpose: To evaluate the effectiveness and safety evaluation of mini-access ureterolithotomy in the management of ureteric calculus. Materials and Methods: This was a cross-sectional study conducted at Department of Urology, Regional Institute of Medical Sciences, Imphal. A total number of one hundred and forty three patients with radiologically confirmed ureteral calculus (size > 1 cm) were enrolled in this study. Results: The mean age of male and female patients was 44.97 ± 11.24 and 43.89 ± 14.49 years, respectively. In the majority of cases stone was in the upper ureter irrespective of the side. The stone size ranged from 10 to 30 mm in diameter. The most common indication for open mini-access ureterolithotomy in the present study was impacted large stone (45%). The mean operation duration was 25.39 ± 5.11 min, with an incision length of 4.78 ± 0.25 mm; the estimated blood loss was 50.55 ± 8 mL and none of the patient’s required post-operative blood transfusion. The overall complication rate was 5.6%. Conclusion: Open mini-access ureterolithotomy is a safe procedure with fewer complications and cosmetically acceptable results. Although in this minimally invasive era, the specific indications for open stone surgery are a few, but when the situation mandates, an open mini-access ureterolithotomy might be considered the best option.